Intracerebroventricular administration of N-acetylaspartylglutamate (NAAG) peptidase inhibitors is analgesic in inflammatory pain - Kozikowski Alan; Yamamoto Tatsuo; Zhou Jia; Neale Joseph H (SAGE Publishing, 2008)
Abstract Background The peptide neurotransmitter N-Acetylaspartylglutamate (NAAG) is the third most prevalent transmitter in the mammalian central nervous system. Local, intrathecal and systemic administration of inhibitors of enzymes that inactivate NAAG decrease responses to inflammatory pain in rat models. Consistent with NAAG's activation of group II metabotropic glutamate receptors, this analgesia is blocked by a group II antagonist. Results This research aimed at determining if analgesia obtained following systemic administration of NAAG peptidase inhibitors is due to NAAG activation of group II mGluRs in brain circuits that mediate perception of inflammatory pain. NAAG and NAAG peptidase inhibitors, ZJ43 and 2-PMPA, were microinjected into a lateral ventricle prior to injection of formalin in the rat footpad. Each treatment reduced the early and late phases of the formalin-induced inflammatory pain response in a dose-dependent manner. The group II mGluR antagonist reversed these analgesic effects consistent with the conclusion that analgesia was mediated by increasing NAAG levels and the peptide's activation of group II receptors. Conclusion These data contribute to proof of the concept that NAAG peptidase inhibition is a novel therapeutic approach to inflammatory pain and that these inhibitors achieve analgesia by elevating synaptic levels of NAAG within pain processing circuits in brain.